EU banks' journey towards an enhanced capital framework - Alessandra Melis; Katrin Weissenberg (European Banking Authority (EBA), 2019)
This paper outlines the development of the European Pillar 2 framework and EU banks' capital positions since 2014. Motivated by concerns that have been raised over the years about excessive levels of required capital imposed on EU banks, we provide empirical evidence on the positioning of EU banks' capital levels relative to their requirements and expectations. Taking advantage of the information gathered by the EBA through supervisory reporting and a unique dataset collected as part of the EBA's policy work on Pillar 2 guidance, we perform a descriptive analysis of the capital margins that banks held in Q3 2017. We find that EU banks generally held ample margins of capital above regulatory requirements and expectations. As expected, we observe at times substantial differences across banks and countries.
Keywords: 330; Pillar 2 Framework; capital requirements; P2R; P2G; capital levels; capital margins; capital composition; transparency